The Effect of Vocabulary Self-Collection Strategy on English Vocabulary Mastery: A Study of the Indonesian High School Students - Marlia Marlia (FOSTER: Journal of English Language Teaching, 2024)
This study examines the effectiveness of the Vocabulary Self-Collection Strategy (VSS) in improving vocabulary mastery among first-grade students at SMAN 1 Bontomarannu. Vocabulary is essential for language proficiency, supporting communication and comprehension across listening, speaking, reading, and writing. However, traditional teaching methods, often focused on rote memorization and teacher-centered instruction, lack interactivity and fail to promote meaningful learning or long-term retention. Using a quasi-experimental design, the study compared two groups: an experimental group applying VSS and a control group following conventional methods. VSS actively engaged students in selecting, analyzing, and internalizing vocabulary from contextual readings, fostering collaboration and autonomy. In contrast, the control group relied on direct instruction and memorization. Results showed significant improvements in vocabulary comprehension and retention among the experimental group, with higher post-test scores compared to the control group. Retention tests conducted a month later confirmed that the experimental group retained more vocabulary, demonstrating the long-term benefits of VSS. This interactive, student-centered approach not only enhances vocabulary acquisition but also promotes independent learning and sustained engagement. By encouraging active participation, VSS empowers learners to take ownership of their learning, making it a valuable strategy for improving language outcomes in diverse educational contexts.